TRADISI MANGANGGAP PADA KOMUNITAS BATAK DI BENGKONG INDAH KOTA BATAM (STUDI TENTANG PERUBAHAN SOSIAL) - Gilbert Fortyanus Nababan; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study is about “Manganggap Tradition on Batak Community at Bengkong Indah Batam City (Study of Social Change)”. Which was this research aimed to explained how manganggap tradition changes in batak community at Bengkok Indah Atas. In this research, writer used qualitative method which gain some descriptive data in form of written words and explained data through logical reasons, to got logical conclusions about analysis data, so it can describe systematically situation using interview, observation, and documentation. Based on result of research tradition changes where indicate some elements in the tradition understanding that is not like the indigenous one, and also the gambling behavior that Batak community at Bengkong Indah Atas itself. Beside the elements that indicated tradition changes, there are some supplementary factors that caused why manganggap culture shifted on Batak community at that Bangkok Indah Atas itself. The reasons are the modern era where caused ethnic cultures already abandoned. Then economically which caused elements and functions of that tradition shifted. And the last, the gambling habits of that community, where they take advantages of tradition implementation venue to distributed their gambling habits.Keyword: Culture, Batak Community, Gambling